Modeling and Simulation of the 50 MW Molten Salt Solar Tower Power Plant in Delingha - Spiros Alexopoulos; Guan Chen (SolarPACES Conference Proceedings)
As a form of renewable energy, concentrated solar power (CSP) is a stable, continuous and dispatchable renewable energy generation technology. By equipping large capacity molten salt storage, CSP has many advantages compared to traditional fossil fuel power plant in terms of electricity quality, like gird-friendly production and very low carbon omission during lifetime. In recent years, many developing countries like Saudi and Morocco made ambitious development goals for CSP as well as on of the G20 lands, China. The SUPCON Delingha 50 MW MS ST CSP Plant is one of the first batch of 20 CSP demonstration projects in China. The solar tower power plant has an installed capacity of 50 MW and includes a 7-hours molten salt storage system. A model of SUPCON Delingha 50 MW MS ST plant was developed with SAM and a simulation took place in order to calculate the annual electrical output performance of the commercial power plant. The simulated result is only 3.6 GWhe less than the design value. The difference, which is less than 5% between the simulation and design value, is caused due to the lack of information.